The evolving role of multilateral development banks: History and prospects - Jannik Lindbaek; Guy Pfeffermann; Neil Gregory (EIB Papers, 1998)
Like all institutions, international financial institutions (IFIs) (1) are creatures of their past. Their organisation and orientation reflect the economic and political contexts in which they were born and evolved. So, too, will their future be shaped by global trends and the ways they respond to them. In this paper, we trace some of the salient themes from the evolution of the role of IFIs, and identify emerging challenges and future directions as they move into the 21st century. Reflecting our background, we give particular emphasis to their support for private enterprise in developing countries, and to the experience of the International Finance Corporation (IFC) and the World Bank Group.
Keywords: 330; Entwicklungsbank; Entwicklungsorganisation; Welt